DEVELOPMENT OF A NUMERICAL METHODOLOGY FOR THE ANALYSIS OF AERODYNAMICS SURFACES (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The cars aerodynamics study aims to evaluate the distribution of pressure and shear stress through the passage of the ï¬‚uid on its surface. With a laminar ï¬‚ow in this passage, the loss of performance by the drag is minimized and hence there is a lower fuel consumption. Good performance in high-speed corners is due to the aerodynamic development, since it aims to keep the vehicle in contact with the ground all the track. The main factor that contributes to a better tyre grip is the force that the vehicle imposes on the ground. One way for maximizing this force without increasing its mass, is the use of aerodynamic forces seeking maximum lift along with the lower drag force. The use of airfoils is therefore a challenge to find a balance between them. Due to high project costs for manufacturing and testing, carrying out the development in computer programs is an economical way to improve the car’s aerodynamics. This paper aims to develop a methodology for computer simulation of aerodynamic surfaces. It is important to mention this is a complementary work to the use of wind tunnels, not replacing, but providing an economical alternative with satisfied numerical precision in the design of aerodynamic surfaces.